Proposed upgrading of information centre at Lot P7, Jalan Indah 14/12,40000 Shah Alam, Selangor for Tourism Selangor Sdn. Bhd. / Noor Liana Mohd Hashim - Mohd Hashim, Noor Liana (Faculty of Architecture, Planning and Surveying, 2012)
The final project is an education towards the student’s knowledge about whole aspect on interior design that had been learnt from basic to the final presentation. This practice student to do some research based on their proposal. Student should fulfill all the requirement needed and follow all the steps. This report is on proposed upgrading information centre at Lot P7, Jalan Indah 14/12, Seksyen 14, 40000 Shah Alam, Selangor for Tourism Selangor Sdn. Bhd. The aim of this project is to create the new environment to facilitate tourist to get information about Selangor. Information centre is a place where people collect information about something at some place. The proposed site is located at Seksyen 14, Shah Alam which opposite of the MBSA building. The total area of the building is 6912 square feet. In order to complete the project, student required to do data collection as the reference. First thing need to do at the beginning af the project is to meet the client. After get the approval from the client, student needs to measure the existing building or search the existing drawing from authorities. Then continue with site analysis and some research for further information. Overall, proposed of this project is to attract more tourist come over to Selangor as Selangor has many fascinating destination.